A study on the Implementation Path of Higher Vocational Colleges to Carry out Social Science Education Services for Young People Under the Background of New Media - Wang, Lijun; Liu, Minmin (Journal of Research in Vocational Education, 2024)
Carrying out science popularization education is of great significance to broaden the knowledge of young people, improve scientific literacy, enhance science popularization awareness and promote social progress. Combining the dissemination advantages of youth social science popularization education under the background of new media and the professional characteristics of higher vocational colleges, this paper analyzes the existing problems, strengthens the development of science popularization education by constructing a vocational and general education integration system; establishes a professional science popularization education service teaching staff, jointly develops high-quality courses; improves the science popularization education method, strengthens interactive communication and improves the teaching quality. It enhances the awareness of teachers in higher vocational colleges on the importance of participating in science popularization education services, and at the same time improves their social service capabilities in the process of practice.